Classical Models for Twin Data: The Case of Categorical Data. Issue 6 (2nd November 2021) - Jöreskog, Karl G.
ABSTRACT: The classical models ACE and ADE were used in the 1990's to estimate heredity of a phenotype from data on monozygotic and dizygotic twins. The author extended these models to a model called ACDE with four parameters instead of only three. In that paper, the data were assumed to be continuous. This paper considers the same models in the case where the data is categorical. It is showed how these models can be estimated by maximum likelihood. An example is given based on twin data on BMI from the UK. This is the same data as in the previous paper but in categorized form.